Optimalisasi Peran UMKM dan Tenaga Kerja Wisata dalam Meningkatkan Ekonomi Masyarakat Lokal melalui Pendekatan Hukum Ekonomi Syariah : (Studi Kasus di Wisata Alam Tumpuk Sewu di desa Sidomulyo, Pronojiwo) (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to analyze the role of Micro, Small, and Medium Enterprises (MSMEs) and tourism workers in improving the economy of local communities through the Sharia Economic Law approach, with a case study in the Tumpak Sewu tourist area, Sidomulyo Village, Lumajang. Using descriptive qualitative methods, data was collected through in-depth interviews, observations, and documentation. The results of the study show that MSMEs and tourism workers have a real contribution to increasing income, job creation, and new business growth. However, the application of sharia principles such as muamalah contracts, Islamic business ethics, and management in accordance with sharia maqashid has not been fully internalized by business actors. Most transactions are still informal and have not been legally documented under Islamic law. This research emphasizes the importance of integration between Community-Based Tourism (CBT) and sharia economic principles through training, institutional assistance, and facilitation of access to sharia financing. These findings provide implications for an inclusive, fair, and sustainable sharia-based community economic empowerment model. This research provides a conceptual and practical basis for the development of sharia-based local economies in the community tourism sector.